Investigation of rehydration kinetics of open-sun dried okra samples - Kocabay, Ozlem Gokce; Ismail, Osman (SPRINGER, 2017)
In this study rehydration kinetics of open-sun dried okra, which dried naturally and two pre-treatment, was investigated at 25 and 50 degrees C. By the obtained data, parameters with respect to rehydration kinetics and diffusion mechanism were calculated. In dehydration experiments, it was determined that blanching pre-treatment has influence on the drying time and okra samples were dried at 18 h. On the contrary in rehydration experiments maximum equilibrium rehydration values were achieved with the okras dried naturally. Experimental equilibrium rehydration (R-eq ), theoretical equilibrium rehydration (R-max ) and diffusion coefficient (D) of okra dried naturally at 50 degrees C were calculated as 5.57 (g water/g dry matter), 5.96 (g water/g dry matter) and 2.17 x 10(-10) (m(2)/s), respectively. Rehydration exponent (n) value, which is also important to identify the diffusion type of dried okra, was determined as between 0.332 and 0.383. Because of the exponent value n < 0.50, diffusion was defined as natural Fick type.
Keywords: WATER-ABSORPTION; DRYING CHARACTERISTICS; PRETREATMENTS; DIFFUSION; TRANSPORT; HYDROGELS; GRAIN; RICE; Thermodynamics; Mechanics